Exploring the Rise of the Gig Economy in Nepal: Shifting Dynamics and Implications for the Future of Gig Work - Bishwakarma, Sagar; Devkota, Niranjan; Bista, Smeeth (Journal of Business and Management, 2024)
Background: The gig economy is a labor market that facilitates opportunities for both employers and employees to engage in freelance work contracts instead of full-time, permanent work positions. Objectives: The purpose of this study is to examine the likelihood of workers continuing their participation in Nepal’s emerging gig platforms and to identify the determinants influencing labor supply across various gig sectors. Additionally, the research aims to explore key opportunities, challenges, and support measures necessary to enhance the well-being and sustainability of gig workers in Nepal. Methods: A binary logit regression model was employed to analyze survey-based primary data collected from 386 gig workers in the Kathmandu Valley. The research encompasses five key sectors: ride-sharing platforms, online tutoring services, e-commerce delivery platforms, food delivery services, and freelance work. To ensure statistical robustness, the study incorporated tests for correlation matrices, goodness of fit, multicollinearity, as well as sensitivity and specificity assessments. Results: Freelancing has the highest participation rate, but ride-sharing and e-commerce delivery reduce gig work continuation, with ride-sharing dominating. Employed individuals, driven by income, satisfaction, and household head status, are more likely to continue. Full-time work is common in ride-sharing and delivery, while part-time work is more frequent in freelancing and tutoring. Gig workers earn subsistence income, between 30-40k NPR, with income rising with age, education, transport costs, hours worked, and satisfaction. Conclusion: Nepalese gig workers face substantial challenges. Women are disproportionately under represented. Addressing legal and regulatory challenges, social and health issues, and financial insecurities, Nepal can leverage its gig economy to provide a resilient and inclusive alternative to traditional employment to resolve unemployment across diverse socioeconomic groups. JEL Classification: J22, J24, O17